FILOSOFI TRI HITA KARANA DALAM MENGUNGKAP KONSEP AKUNTANSI HIJAU (STUDI FENOMENOLOGI) - Ni Putu Ayu Kusumawati; Ni Made Wisni Arie Pramuki; Ni Putu Trisna Windika Pratiwi (KRISNA: Kumpulan Riset Akuntansi, 2023)
Sustainability issues that have spread recently have also had an impact on the world of accounting. Previously, the company's annual financial reporting was the prima donna, but now it has been added with the presence of a settlement report as a response to this issue and provides consequences for the emergence of the green accounting concept. Green accounting develops from the basic philosophy that accountants must care about the environment and society. The development of accounting which had moved away from the focus on the social and environmental fields has created a problem because accounting is only limited to technical matters and becomes apathetic towards the conditions in the surrounding environment. Through the Tri Hita Karana phenomenological philosophy study method, researchers are trying to reveal how the concept of green accounting is based on values ​​derived from the teachings of Hinduism. Researchers analyzed data from informants by conducting interviews with experienced subjects in the field of green accounting and interviewing knowledge subjects from accountants, humanists and religionists. The selection of divided methods in order to reveal the values ​​of Hinduism in the concept of green accounting. The concept of green accounting with a phenomenological approach to the Tri Hita Karana philosophy includes 3 main aspects that influence green accounting motives, reporting, recording, summarizing, and recognition. The srada bhakti, yadnya and spiritual aspects are complemented by the green accounting concept which is intended to carry out as best as possible the social and environmental responsibility of an entity. The results of the green accounting concept through the phenomenological approach to the THK philosophy raises a more comprehensive epistemological face because it contains basic aspects that did not previously exist in the conventional green accounting concept